O JK Shopping como um espa??o de lazer na percep????o de seus frequentadores - Assad, Waldir Delgado (2016)
The study aims to identify what is the relationship between the residents of Ceil??ndia, locat??d in the Federal District and the JK Shopping Center and check if this Shopping is understood by this population as a recreational space, understanding this leisure as one of the study of physical education course. 353 attendees were surveyed in this location, which answered a questionnaire and a semi structured research. Data were analyzed statistically by checking the frequency of responses as well as a speech analysis was performed. It was perceived that consumption is not the main factor for the frequency to this space, as well as food court and cinema came before the shops and consumption in the motivation to go the mall. Another important factor was the fact that it is a nearby location, which greatly facilitat??s the frequency to it. The study showed that new times bring new possibilities for leisure and their experiences.